Observed Equatorward Propagation and Chimney Effect of Near‐Inertial Waves in the Midlatitude Ocean. Issue 13 (12th July 2022) - Yu, Xiaolong; Naveira Garabato, Alberto C.; Vic, Clément; Gula, Jonathan; Savage, Anna C.; Wang, Jinbo; Waterhouse, Amy F.; MacKinnon, Jennifer A.
Abstract: The propagation characteristics of near‐inertial waves (NIWs) and how mesoscale and submesoscale processes affect the waves' vertical penetration are investigated using observations from a mooring array located in the northeast Atlantic. The year‐long observations show that near‐inertial motions are mainly generated by local wind forcing, and that they radiate equatorward and downward following several strong wind events (wind stress ≳0.5 N m −2 ). Observational estimates of horizontal group speed typically exceed those of vertical group speed by two orders of magnitude, consistent with predictions from the dispersion relation. Enhanced near‐inertial kinetic energy and vertical shear are found only in mesoscale anticyclones with Rossby number of O(0.1). By contrast, submesoscale motions with order one Rossby number have little effect on the trapping and vertical penetration of NIWs, due to their smaller horizontal scales, shorter time scales, and confined vertical extent compared to mesoscale eddies. Plain Language Summary: Near‐inertial waves (NIWs) are excited mainly by variable winds at the ocean surface and can carry their energy into the ocean interior, thus playing an important role in mixing the deep ocean. However, the propagation behaviors of NIWs, and how such waves are affected by mesoscale and submesoscale processes, are still understudied, especially over periods of months to years. In this study, we examine an annual cycle of wind‐generated NIWs based on moored observations in a typical open‐ocean region of the northeast Atlantic. Our results show that NIWs propagate downward and equatorward following several strong wind events. Enhanced near‐inertial kinetic energy and vertical shear are found preferentially in regions of anticyclonic vorticity with Rossby number of O(0.1). By contrast, submesoscale anticyclones with Rossby number of O(1) are ineffective at trapping and accelerating near‐inertial motions into the ocean interior. This is due to the smaller horizontal scales, shorter time scales, and confined vertical extent of submesoscale motions compared to mesoscale eddies. Our findings highlight the major role of mesoscale anticyclones in draining NIWs from the upper ocean to the ocean interior, and have implications for detecting regions of active turbulent mixing driven by NIWs in the deep ocean. Key Points: We provide observational evidence of downward‐ and equatorward‐propagating near‐inertial waves over a full annual cycle Enhanced near‐inertial kinetic energy and vertical shear are found preferentially in regions of anticyclonic vorticity The chimney effect for near‐inertial waves is very likely controlled by mesoscale, rather than submesoscale, anticyclones